Emission Characteristics of Volatile Organic Compounds from Material Extrusion Printers Using Acrylonitrile–Butadiene–Styrene and Polylactic Acid Filaments in Printing Environments and Their Toxicological Concerns - Yuan Gao; Yawei Xue; Chenyang Sun; Luhang She; Ying Peng (Toxics)
The utilization of 3D printing releases a multitude of harmful gas pollutants, posing potential health risks to operators. Materials extrusion (ME; also known as fused deposition modeling (FDM)), a widely adopted 3D printing technology, predominantly employs acrylonitrile–butadiene–styrene (ABS) and polylactic acid (PLA) as printing materials, with the respective market shares of these materials reaching approximately 75%. The extensive usage of ABS and PLA during the ME process leads to significant volatile organic compound (VOC) emissions, thereby deteriorating the quality of indoor air. Nevertheless, information regarding the emission characteristics of VOCs and their influencing factors, as well as the toxicological impacts of the printing processes, remains largely unknown. Herein, we thoroughly reviewed the emission characteristics of VOCs released during ME printing processes using ABS and PLA in various printing environments, such as chambers, laboratories, and workplaces, as well as their potential influencing factors under different environmental conditions. A total of 62 VOC substances were identified in chamber studies using ABS and PLA filaments; for example, styrene had an emission rate of 0.29–113.10 μg/min, and isopropyl alcohol had an emission rate of 3.55–56.53 μg/min. Emission rates vary depending on the composition of the filament’s raw materials, additives (such as dyes and stabilizers), printing conditions (temperature), the printer’s condition (whether it has closure), and other factors. Additionally, we reviewed the toxicological concerns associated with hazardous VOC species commonly detected during the ME printing process and estimated cancer and non-cancer risks for users after long-term inhalation exposure. Potential health hazards associated with inhalation exposure to benzene, formaldehyde, acetaldehyde, styrene, and other substances were identified, which were calculated based on concentrations measured in real indoor environments. This study provides valuable insights for future research on the development of ME printing technologies and offers suggestions to reduce VOC emissions to protect users.